1993
DOI: 10.1161/01.atv.13.11.1654
|View full text |Cite
|
Sign up to set email alerts
|

Associations of age, adiposity, alcohol intake, menstrual status, and estrogen therapy with high-density lipoprotein subclasses.

Abstract: We used nondenaturing polyacrylamide gradient gel electrophoresis to examine the associations of age, adiposity, alcohol intake, and exogenous estrogen with high-density lipoprotein (HDL) subclasses in 427 members of 51 principally Mormon kindreds. The absorbency of protein stain was used as an index of mass concentrations at intervals of 0.01 nm within five HDL subclasses: HDLj,. (7.2 to 7.8 nm), HDL, b (7.8 to 8.2 nm), HDL,, (8.2 to 8.8 nm), HDL 2a (8.8 to 9.7 nm), and HDL 2b (9.7 to 12 nm). Age and alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
31
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 32 publications
8
31
0
Order By: Relevance
“…This is consistent with our previous observation that postmenopausal estrogen replacement primarily increases HDL 2a [11]. Estrogen and progesterone are elevated during the luteal phase.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with our previous observation that postmenopausal estrogen replacement primarily increases HDL 2a [11]. Estrogen and progesterone are elevated during the luteal phase.…”
Section: Discussionsupporting
confidence: 93%
“…Persons were excluded from this analysis if they reported drinking, smoking, using birth control pills, or taking drugs known to affect plasma HDL. We have previously reported that there were 89 premenopausal women who had regular menstrual periods in this sample [11]. The day of the cycle was determined from the following questionnaire item: "Do you have regular cycles or periods?…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas women had larger HDL particles than men, we found that this sex differential narrowed by ϳ50% with increasing age. Age-related changes in HDL subclasses have been reported by other investigators, with concentrations of HDL 3b increasing after menopause (38 ) and concentrations of small HDL increasing during puberty among boys (39 ). There is also some evidence that HDLcholesterol concentrations are more strongly (inversely) associated with CHD risk among women than men (40 ), and this may, in part, be attributable to the larger mean HDL particle size of women.…”
Section: Discussionmentioning
confidence: 54%
“…Low circulating HDL-C levels are regarded as a major atherosclerotic risk factor (Gordon et al 1977;Gordon et al 1989;Kitamura et al 1994) via the interplay of environmental, nutritional, and genetic factors (Williams et al 1993(Williams et al , 1995Watts 2001). In the present study, circulating HDL-C levels were reduced to a significantly less extent by a LCD in subjects with the G allele than those without the G allele, although weight loss and nutrient intake levels did not differ between genotypes.…”
Section: Discussionmentioning
confidence: 99%